TRANSFORMASI INTEGRATED MARKETING COMMUNICATION DI ERA DIGITAL - Santoso, Prasetya Yoga (JURNAL PUSTAKA KOMUNIKASI, 2018)
This study aims to determine the transformation of Integrated Marketing Communication in the Digital Age and the implementation of business people and the impact of these changes. The findings in this study describe the characteristics of online media and social media that have differences with conventional media. Currently IMC is included in IMC 4.0 where interactions can be done anywhere, anytime, and only with one online media. With the internet network, companies can market their products through online, advertorial, promotion, and sales advertisements directly in one form of media. IMC 4.0 allows only online audiences to be able to make transactions, obtain information, complain, until testimonials. Shifting from the physical store / store and now only being sold via online media where buyers see displays with catalogs, photos, videos, and dimensional and other information. The shift from conventional stores to online sales. Many conventional stores are closed and they set up online shops and online malls.